Comparison of thiobarbituric acid reacting substances and total antioxidant capacity in saliva of smokers and nonsmokers - Mohammad Moballegholeslam; Soleiman Mahjoub; Mehrdad Taghibakhsh; Ali Bijani (Babol University of Medical Sciences, 2018)
Introduction: The aim of this study was to evaluate thiobarbituric acid reactive substances (TBARS) as lipid peroxidation marker and total antioxidant capacity(TAC) in saliva of smoker and non-smoker men. Materials & Methods: This case-control study was performed on 104 men including smoker (52) and non-smoker (52) men, referred to the Oral Medicine Department in Babol Faculty of Dentistry. 2 ml of unstimulated saliva was collected and specimens were transferred to the Biochemistry Laboratory using dry ice and freezed. Data were analyzed using SPSS 18 and Mann Whitney test. Results: Findings indicated that the levels of TBARS and TAC in saliva of smokers were significantly higher than control group. Conclusion: Higher level of TBARS in smokers can show the evident and dangerous role of cigarette and its chemical compounds, and increased level of TAC in smokers can prove the hypothesis of compensatory mechanism of antioxidant system.